The Performance of Powerlifting Athletes During Their Lifetime - Hernández Ugalde, José Alfredo (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2021)
This research performed data mining for men and women powerlifters for the categories of Equipped Powerlifting, Classic Powerlifting, Equipped Bench Press, and Classic Bench Press, recognized by the International Powerlifting Federation (IPF). It then conducted a nonlinear regression analysis based on age versus mean scores in terms of Wilks Points, IPF Points, and IPF GoodLift Points to obtain the fitted curve and the age of peak performance for each category. Overall, the performance for all categories of men and women in powerlifting and bench press starts with exponential growth from youth until close to the third decade, showing a peak performance between 27.67 to 31.50 years of age, and then a linear decrease during maturation and older age. Comparisons between men and women and between equipped and classic athletes do not show meaningful differences in age of peak performance, suggesting the same biological clock in terms of aging. The sport of powerlifting offers a useful model to study human beings’ growth, maturation, and aging.